Determination of band offset in InP/YSZ hetero-junction by X-ray photoelectron spectroscopy. (January 2018) - Yao, Jian Ke; Ye, Fan; Wang, Bo; Cai, Xing-Min; Fan, Ping
Abstract: Y-stabilized ZrO2 (YSZ) was one of the familiar high dielectric constant films used in InP field effect transistors. However, the structure and optical properties of YSZ film deposited on InP substrate were rarely reported. The band offsets in InP/YSZ hetero-junction was an important parameter, which had not been measured. In the work, YSZ films were deposited on InP substrates by sputtering. The optical properties and structures of YSZ films and InP/YSZ interface were characterized. X-ray photoelectron spectroscopy was used to measure the energy discontinuity in the valence band of the InP/YSZ hetero-structure. A value of 1.4 eV was obtained with In 3d5 as the reference energy level. With the band gap of 5.8 eV for YSZ and 1.3 eV for InP, this indicated a conduction band offset of 3.1 eV in the system. Highlights: The band offsets of InP/YSZ hetero-structure were measured by X-ray photoelectron spectroscopy. The optical properties and structures of YSZ films on InP by Sputtering were characterized. The interfacial structures of ultrathin YSZ films on InP by Sputtering were characterized.